The impact of the anti-corruption campaign on energy efficiency: Evidence from prefecture-level cities in China - Ji, Hongkun (Frontiers in Environmental Science, 2022)
China's development has been accompanied by serious corruption and environmental pollution. Corruption is particularly prevalent in the energy sector, where it can bring very substantial benefits. However, corruption in the energy sector can lead to serious misallocation of energy, resulting in wasteful and inefficient use of energy. With the rise of the anti-corruption campaign, there is an urgent need to explore the impact of the anti-corruption campaign (ACC) on energy efficiency (EE). This paper investigates whether and how the ACC affects EE in China. Leveraging a staggered difference-in-differences (DID) model, we estimate the causal effect of the ACC in China on EE. Our results indicate that the ACC significantly improves EE, which is robust to a battery of robustness tests, such as parallel trend test, placebo test, excluding other policies, and substituting the explained variable. The positive relationship is correlated to reducing rent-seeking behavior, promoting innovation capacities, and upgrading industrial structure within a city. The heterogeneous results suggest that the effect of the ACC on EE improvement is more pronounced in big cities, cities located in the central, cities with high fiscal expenditures and low R&D expenditures. The results of this paper show that we must be tenacious in the anti-corruption campaign to establish a clean government and increase energy efficiency in order to achieve sustainable development.